Nonlinearities Distribution Homotopy Perturbation Method Applied to Solve Nonlinear Problems: Thomas-Fermi Equation as a Case Study - U. Filobello-Nino; H. Vazquez-Leal; K. Boubaker; A. Sarmiento-Reyes; A. Perez-Sesma; A. Diaz-Sanchez; V. M. Jimenez-Fernandez; J. Cervantes-Perez; J. Sanchez-Orea; J. Huerta-Chua; L. J. Morales-Mendoza; M. Gonzalez-Lee; et al. (Journal of Applied Mathematics)
We propose an approximate solution of T-F equation, obtained by using the nonlinearities distribution homotopy perturbation method (NDHPM). Besides, we show a table of comparison, between this proposed approximate solution and a numerical of T-F, by establishing the accuracy of the results.